The Relationship of VO2 Max Levels, Flexibility, Arm Power and Speed of Acceleration with the Softball Skills of Male Athletes Palopo City, South Sulawesi - Akbar Azis; Sudirman Burhanuddin; Nuhkrawi Nawir; Muh. Adnan Hudain (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
Analysis of VO2 Max level, flexibility, arm power and acceleration speed on the skills of male softball athletes in the city of Palopo, South Sulawesi. Thesis. Physical and Sports Education Study Program, Makassar State University Postgraduate. This study aims to determine the relationship between VO2 Max, flexibility, arm power and acceleration speed on the skills of male athletes in the city of Palopo. This study uses correlational research. The population of this study was 20 softball athletes from the city of Palopo. The research sample is 20 Palopo City softball athletes. The data analysis technique used is the inferential test on the regression test statistic. The results of the study show that 1) There is a sufficient and significant relationship between VO2 Max and the skills of male softball athletes in the city of Palopo. 2) There is a strong and significant relationship between flexibility and the skills of male athletes from the city of Palopo. 3) There is a strong and significant relationship between arm power and the skills of the Palopo City male athletes. 4) There is a sufficient and significant relationship between the speed of acceleration and the skills of the Palopo City male athletes.